FOUCAULDIAN PANOPTIC GAZE IN NADINE CHARACTER KELLY FREMON CRAIG’S THE EDGE OF SEVENTEEN (2016) - Aisha Adha Ainiya; Abd Hannan EF; Hasbi Assiddiqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Film studies have increasingly adopted social theory as a framework for visual analysis; however, the application of Michel Foucault's concept of panopticism to realist coming-of-age cinema remains limited, particularly in explaining how disciplinary power operates through ordinary social interactions rather than formal institutions. This study aims to examine how panoptic mechanisms are visually represented in Kelly Fremon Craig's The Edge of Seventeen (2016) and to demonstrate the usefulness of Foucauldian theory in realist film analysis. Employing a qualitative descriptive approach with document analysis, the research analyzes six selected scenes through close reading of cinematic elements, including mise-en-scène, shot scale, camera angle, and spatial design. The findings reveal that visual techniques such as shallow depth of field, high-angle framing, extreme close-up, and medium tracking shots, combined with everyday settings including parties, bathrooms, cafeterias, and classrooms, construct conditions of asymmetric visibility, self-monitoring, and normalizing judgment. Rather than relying on explicit authority figures, the film depicts discipline as emerging through peer observation and internalized social expectations. These visual strategies encourage characters to regulate their own behavior while reinforcing dominant social norms. The study concludes that Foucauldian panopticism provides a systematic analytical framework for understanding how realist coming-of-age films naturalize disciplinary power through cinematic form and everyday spaces.